Does spatial disaggregation matter in job creation and destruction flows? - Elena Cefis; Roberto Gabriele (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
The paper investigates the changes in job creation and destruction flows considering a very disaggregate level of analysis. If institutional setup plays a more important role compared to other factors, than at lower levels of aggregation we should observe that job flows regularities are in line with national ones. We explore the issue using a unique database on the population of firms in Trentino (a North-Eastern Province of Italy) from 1991 to 2001. We find that: (a) job flows show a fractal nature, i.e. many regularities appear to be scale invariant (magnitude of flows and their persistence). In particular job flows magnitude is in line with the average values for Italy; (b) there are some qualifications to fractality: entrant firms' contribution to job creation process is lower than the corresponding contribution at national level, whereas the job destruction share accounted for by exit firms is around 30%, in line with stylized facts; (c) size and age shape the job flows; (d) shifts of jobs between macro sectors are rare.
Keywords: C34; J23; L11; 330; labour reallocation; job flows; sample selection; two-stage Heckman estimator; Arbeitsnachfrage; Räumliche Verteilung; Stichprobenverfahren; Trient (Provinz); Italien